Local Government's Role in Developing Natural Tourism in Pasuruan Regency - Isnaini Rodiyah; Tian Larasati (Research Parks Publishers, 2022)
This study investigates the role of village government in the development of Coban Binangun waterfall tourism, employing a qualitative approach with descriptive methods. Data were collected through interviews, observations, and documentation, and analyzed using an interactive model involving data reduction, presentation, and conclusion drawing. The theoretical framework utilized motivators, facilitators, and dynamics as indicators of governmental roles. Findings indicate that while the village government plays a pivotal role as motivator, facilitator, and dynamist in tourism development, challenges persist, hindering optimal outcomes. This study underscores the importance of governmental support in fostering sustainable tourism practices and community engagement, offering insights applicable to similar contexts globally.